2022
DOI: 10.3390/cancers14133277
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Diseases and Risk of Head and Neck Cancer: A Cohort Study Analyzing Nationwide Population-Based Data

Abstract: The aim of the study was to investigate the association between metabolic diseases and the risk of head and neck cancer (HNC) using nationwide population-based big data. This retrospective cohort study was conducted using the Korean National Health Insurance Service health checkup database. A total of 4,575,818 participants aged >40 years who received a health checkup in 2008 were enrolled, and we studied the incidence of HNC until 2019. We analyzed the risk of HNC according to the presence of metabolic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…T2DM is marked by hyperglycemia, insulin resistance, decreased insulin secretion, and dyslipidemia, including elevated triglyceride levels and low high-density lipoprotein cholesterol [9][10][11][12]. Studies have suggested an association between DM and HNC [13][14][15][16]. Tseng et al [13] found that individuals newly diagnosed with DM had a 1.47-fold higher overall incidence of HNC compared to those without DM, regardless of factors such as age, sex, geographic location, income, and coexisting conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T2DM is marked by hyperglycemia, insulin resistance, decreased insulin secretion, and dyslipidemia, including elevated triglyceride levels and low high-density lipoprotein cholesterol [9][10][11][12]. Studies have suggested an association between DM and HNC [13][14][15][16]. Tseng et al [13] found that individuals newly diagnosed with DM had a 1.47-fold higher overall incidence of HNC compared to those without DM, regardless of factors such as age, sex, geographic location, income, and coexisting conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis study involving more than 51,496 individuals with HNC cancer in East Asia revealed an association between DM and elevated HNC risk [14]. A South Korean national cohort study found that diabetes mellitus (DM) increases the risk of head and neck cancer (HNC) in both genders, with a higher risk compared to moderate alcohol consumption and equal to the risk from cigarette smoking [16]. Therefore, identifying a medication that could mitigate or eliminate the risk of HNC in patients with T2DM is imperative.…”
Section: Introductionmentioning
confidence: 99%